Genotypic, fertility, and environmental effects on grain yield of bread wheat and its quality in the drysubhumid pampas region (Semiárida, 2020)
Bread wheat is important in the subhumid dry Pampas region. It has great interannual variability in grain yield and quality. The objective was to evaluate the effect of the year, the genotype and the nitrogen fertilization in the grain yield and its quality. The tests were carried out in the Faculty of Agronomy of the UNLPam (36° 32' 49 "S; 64° 18' 20" W) for 6 years, with 5 genotypes. The fertilized treatment was added 100 kg.ha-1 of broadcast urea in early tillering. The growth season exerted a great effect on grain yield. The test weight was very influenced by the growth season and also by the genotype. On the percentage of protein, instead, fertility was the most important factor. There was no relationship between quality group and protein percentage. The nitrogen fertilizer in tillering increased the six years the percentage of protein, whereas, the yield alone in three. Increased consumptive use during grain filling caused increased test weight and decreased protein content in both fertility treatments. The increase in temperature during the filling decreased the test weight and increased the percentage of protein, only in the fertilized treatment.
Keywords: Triticum aestivum; production; test weight; protein